(untitled) (Annual of the Faculty of Philosophy in Skopje, 2018)
The proportion of higher education students with disabilities is increasing at university level. In Macedonia, there are no statistics about the number of students with disabilities included in the academic institutions. The inadequate accessibility of higher education institutions, the lack of support, the negative social attitudes and social isolation, as well as the low financial capacity influence the success of students with disabilities and affect their inclusion in the higher education. Тhis study aims to conduct an in-depth review of some of these challenges that are present in the higher education of students with disabilities. A detailed analysis of 11 publications was performed. We can conclude from those publications that faculty members demonstrate generally positive attitudes towards students with disabilities, with some research indicating less favourable attitudes towards those with “nonvisible” disabilities, such as learning disabilities. Also, there are conflicting results as to whether students with disabilities have an equivalent academic performance with those without disabilities.